Characterization and functional significance of glucocorticoid receptors in patients with major depression: Modulation by antidepressant treatment - Calfa, Gaston Diego (2003)
Hyperactivity of the hypothalamic pituitary adrenal (HPA) axis in patients with major depression is one of the most consistent findings in biological psychiatry. Experimental data support the idea that glucocorticoid-mediated feedback via glucocorticoid receptors (GR) is impaired in major depression. The aim of the present work was to assess the putative changes in GR density of peripheral blood mononuclear cells (PBMCs) in a group of patients with major depression and to determine modulation of these GR sites by antidepressant treatment. In addition, susceptibility of PBMCs to glucocorticoid effects was also studied using a functional end-point analysis in vitro, such as cortisol inhibition of mitogen-induced lymphocyte proliferation. Cortisol levels were also measured before and after dexamethasone suppression test (DST). The results showed a decrease in GR density in depressed patients compared with healthy subjects, mainly in those patients that showed basal cortisol levels in the upper normal range and were refractory to DST. Regarding the functional significance of this variation, two representative groups emerged from our study: a) free-medication patients with GR function comparable to healthy controls, and b) patients showing diminished GR activity. These results suggest a lack of relationship between GR density and cortisol-induced inhibition of lymphocyte proliferation. Patients treated with different antidepressant drugs showed a marked increase in the number of GR sites per cell compared to non-treated. Interestingly, this increase was even higher than in normal subjects. Hence, restoration of GR density after an efficient antidepressant treatment could be an index of an effective modulatory action of drugs on GR expression and highlights the possibility that GR levels might be used as markers of a successful treatment. © 2003 Elsevier Science Ltd. All rights reserved.